Cancer incidence in relation to fluoride level in water supplies. - Kinlen, L (1974)
The incidence of cancer of the thyroid, kidney, stomach, esophagus, colon, rectum, bladder, bone and breast in areas of England with a high natural fluoride level in the water was compared with that in areas with low water fluoride levels. No differences were detected. Similarly, no differences were found in cancer incidence between fluoridated and control districts in England and Wales, the U.S.A., Holland and New Zealand.